Analisis Dampak Pembangunan Sekat Kanal Terhadap Fluktuasi Muka Air Tanah (Studi Kasus: Desa Lukun, Kabupaten Kepulauan Meranti) - Hidayati, Nur; Rinaldi, Rinaldi; Sutikno, Sigit (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Peat restoration are needed to stop and curb the rate of further damage and rehabilitate peat ecosystems. The Peat Restoration Agency Republic of Indonesia has implemented peat restoration efforts one of them through rewetting activities within the territory of the Peat Hydrological Unity (PHU). The peat land village of Lukun village has burnt and degraded over years. With the rewetting of the peat, it is expected that the hydrologically disturbed peat will be improved and the peat will remain in wet conditions so that the degradation rate and potential of peat fires can be prevented. Therefore, the analysis of the impact of the development of canal against groundwater table using the dipwells tool to monitor and evaluate post-construction of the channel canal. Testing is done by varying the opening of the door on the channel canal. The results obtained from dipwells in the form of graph of groundwater fluctuation from several channel canals with variation of open cap of channel of the channel influenced by rainfall, hydrotopography and characteristic on peatland. Keywords: Peat Hydrological Unity, Groundwater Table, Canal Blocking, Fire of Peat Land.